Variation in APOL1 Contributes to Ancestry-Level Differences in HDLc-Kidney Function Association. (2nd September 2012) - Bentley, Amy Rebecca; Doumatey, Ayo P.; Chen, Guanjie; Huang, Hanxia; Zhou, Jie; Shriner, Daniel; Jiang, CongQing; Zhang, Zhenjian; Liu, Guozheng; Fasanmade, Olufemi; Johnson, Thomas; Oli, Johnnie; et al.
Abstract : Low levels of high-density cholesterol (HDLc) accompany chronic kidney disease, but the association between HDLc and the estimated glomerular filtration rate (eGFR) in the general population is unclear. We investigated the HDLc-eGFR association in nondiabetic Han Chinese (HC, n = 1100 ), West Africans (WA, n = 1497 ), and African Americans (AA, n = 1539 ). There were significant differences by ancestry: HDLc was positively associated with eGFR in HC (β = 0.13, P < 0.0001 ), but negatively associated among African ancestry populations (WA: −0.19, P < 0.0001 ; AA: −0.09, P = 0.02 ). These differences were also seen in nationally-representative NHANES data (among European Americans: 0.09, P = 0.005 ; among African Americans −0.14, P = 0.03 ). To further explore the findings in African ancestry populations, we investigated the role of an African ancestry-specific nephropathy risk variant, rs73885319, in the gene encoding HDL-associated APOL1. Among AA, an inverse HDLc-eGFR association was observed only with the risk genotype (−0.38 versus 0.001; P = 0.03 ). This interaction was not seen in WA. In summary, counter to expectation, an inverse HDLc-eGFR association was observed among those of African ancestry. Given the APOL1 × HDLc interaction among AA, genetic factors may contribute to this paradoxical association. Notably, these findings suggest that the unexplained mechanism by which APOL1 affects kidney-disease risk may involve HDLc.